2008
DOI: 10.1111/j.1365-2915.2008.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular detection of Theileria and Babesia in questing ticks from northern Spain

Abstract: A total of 562 questing adult ixodid ticks, collected during 2003-05 in 10 recreational mountain areas in northern Spain, were analysed for piroplasm infection. Reverse line blot (RLB) analysis using a panel of probes for 23 piroplasm species identified 16 different piroplasms, with an overall prevalence of 9.3%. Most were Theileria spp.-positive (7.7%), 3.0% were positive for Babesia spp. and 1.4% of ticks harboured both genera. Ixodes ricinus (Linnaeus, 1758), the most abundant tick in the vegetation, ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 28 publications
(77 reference statements)
5
49
1
1
Order By: Relevance
“…Nevertheless, we were not able to identify any study conducted in Portugal that has isolated T. annulata from R. bursa ticks. T. equi (formerly known as Babesia equi) can be naturally transmitted by ticks of the family Ixodidae (Stiller et al, 2002) and R. bursa has been implicated as the vector of piroplasmosis caused by T. equi in horses in Spain and Iran (Abedi et al, 2014;Garcia-Sanmartin et al, 2008). Similarly, we have found T. equi in ticks of this species infesting horses.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Nevertheless, we were not able to identify any study conducted in Portugal that has isolated T. annulata from R. bursa ticks. T. equi (formerly known as Babesia equi) can be naturally transmitted by ticks of the family Ixodidae (Stiller et al, 2002) and R. bursa has been implicated as the vector of piroplasmosis caused by T. equi in horses in Spain and Iran (Abedi et al, 2014;Garcia-Sanmartin et al, 2008). Similarly, we have found T. equi in ticks of this species infesting horses.…”
Section: Discussionsupporting
confidence: 71%
“…During our study we have found an equivalent ratio of male: female. Although a similar ratio of male: female has been reported (Garcia-Sanmartin et al, 2008), most studies report that the number of males generally outnumbers the number of females (Moshaverinia et al, 2012;Papadopoulos et al, 1996;Yeruham et al, 1996). As mentioned, the primary hosts of this tick species include cattle, sheep, and goats; and less frequently dogs and smaller mammals, such as rabbits (de la Fuente et al, 2004a;Masala et al, 2012;Mihalca et al, 2012;Psaroulaki et al, 2006;Santos-Silva et al, 2011;Satta et al, 2011;Walker et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has caused important economic losses in the horse industry, being a serious threat to the horse raising industry and international movement of horses (FRIEDHOFF et al, 1990). Previous studies have demonstrated losses due to treatment costs, recuperation time and low athletic performance (GARCÍA-SANMARTÍN et al, 2008). In addition, equine piroplasmosis creates difficulty in animals trading and restrictions regarding import/export of animals, as well as participation in international competitions, given that infected animals are prevented from entering countries that are disease-free (FRIEDHOFF et al, 1990;KNOWLES, 1996).…”
mentioning
confidence: 99%
“…In one previous report (BALDANI et al, 2010) the high positivity rate for T. equi was attributed to the management of horses, which appears to be an important factor for the prevalence of T. equi infections. Additionally, climatic factors such as temperature, relative humidity, altitude and high rainfall influence the habitat of the main tick/vector species that parasite horses (GOLYNSKI et al, 2008). It has been demonstrated that when horses have direct or indirect contact with cattle and there is no rigorous tick control program, T. equi infection rates are much higher (HEUCHERT et al, 1999;KERBER et al, 1999).…”
mentioning
confidence: 99%